In vivo performance of hierarchical HRP-crosslinked silk fibroin/β-TCP scaffolds for osteochondral tissue regeneration - Ribeiro, Viviana Pinto (2019)
Background: Osteochondral defects (OCD) can affect the articular cartilage and subchondral bone tissues, which requires superior therapies for the simultaneous and full restoration of such structurally and biologically different tissues. Methods: Tissue engineered OC grafts were prepared using a horseradish peroxidase (HRP) approach to crosslink silk fibroin (HRP-SF) as the articular cartilage-like layer and an underlying HRP-SF/ZnSrTCP subchondral bone-like layer (HRP-SF/dTCP), through salt-leaching/freeze-drying methodologies. In vivo OC regeneration was assessed by implantating the hierarchical scaffolds in rabbit critical size OC defects, during 8 weeks. A comparative analysis was performed using hierarchical OC grafts made of pure Î²-TCP (HRP-SF/TCP). Results: The hierarchical scaffolds showed good integration into the host tissue and no signs of acute inflammatory reaction, after 8 weeks of implantation. The histological analyses revealed positive collagen type II and glycosaminoglycansâ formation in the articular cartilage-like layer. New bone ingrowthâ s and blood vessels infiltration were detected in the subchondral bone-like layers. Conclusions: The proposed hierarchical scaffolds presented an adequate in vivo response with cartilage tissue regeneration and calcified tissue formation specially promoted by the ionic incorporation into the subchondral bone layer, confirming the hierarchical structures as suitable for OCD regeneration.